INQUIRY-BASED LEARNING AS A CATALYST FOR DEVELOPING SCIENCE PROCESS SKILLS IN SCIENCE EDUCATION: A COMPREHENSIVE SYSTEMATIC REVIEW - Muzafar, Nurashikin; Ahmad, Nur Jahan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The rapid evolution of science education necessitates innovative teaching approaches to equip students with essential scientific process skills (SPS). Despite the growing adoption of Inquiry-Based Learning (IBL), there remains a lack of comprehensive synthesis regarding its effectiveness in enhancing SPS, particularly in the context of technological integration. This systematic review aims to address this gap by (i) identifying current issues in SPS development, (ii) evaluating the objectives and methodologies of recent IBL studies, and (iii) synthesizing key findings to inform best practices. A total of 178 articles published between 2019 and 2023 were retrieved from Scopus and Web of Science databases, with 18 studies meeting the inclusion criteria through a rigorous PRISMA-based selection process. The analysis reveals that guided inquiry, supported by technology and scaffolded instruction, is the most effective IBL approach for fostering SPS among secondary school students. Key findings are categorized into three main themes: active engagement and hands-on experience, integration of modern technological tools, and structured guidance. The review highlights the importance of aligning IBL strategies with curriculum objectives, providing targeted teacher training, and addressing challenges such as resource limitations and varying student readiness. This study offers actionable recommendations for educators and policymakers to enhance SPS through effective IBL implementation and suggests future research directions to further optimize science education in a technology-driven era.